Constellations, technicality, iconisation and Eskom: A case from South Africa's Business Day. Issue 2 (3rd April 2022) - Siebörger, Ian; Adendorff, Ralph D.
Abstract: This article uses Legitimation Code Theory (LCT) and systemic functional linguistics (SFL) to explore interactions between various resources for building economic and political knowledge in a 2015 article from Business Day, a South African newspaper, concerning the country's energy crisis. We use LCT to observe how three constellations are built in the article: a 'developmental state' constellation; a 'neo-liberal' constellation; and another underarticulated constellation that selectively draws ideas from both the preceding constellations. These constellations are built through the unfolding of the text using various linguistic resources, which we describe using SFL, including technicality and iconisation. We identify instances where words are charged with both ideational and axiological meaning concurrently, challenging existing understandings of the process of iconisation.